Effect of Cu-bearing precipitates on mechanical, wear and antibacterial properties of Ti–Nb–Zr–Cu alloy - Xiangyi Wang; Zonghao Li; Changbin Zhang; Hongyan Hu; Junkui Ren; Zhitong Kui; Lei Zhang; Zhengyuan He; Yehua Jiang (Journal of Materials Research and Technology)
The Cu addition could affect mechanical, wear and antibacterial properties of Ti–Nb–Zr alloy due to the Cu-bearing precipitates. In this work, the precipitation type, morphology and distribution of Cu-bearing precipitates in the Ti–35Nb–7Zr–10Cu alloy were controlled via heat treatment at 800, 850, 900, 950 and 1000 °C followed by water cooling. The effects of Cu-bearing precipitates on the mechanical, wear, and antibacterial properties of Ti–Nb–Zr–Cu alloy were investigated. Results showed that the main Cu-bearing precipitates were composed of Ti2Cu and Cu8Zr3 phases. With the increase of heat temperature, the Ti2Cu phase decreased while the Cu8Zr3 phase increased. The morphology of Cu-bearing precipitates changed from network to spherical. The HT1000 sample had the lowest elastic modulus of 46 ± 1 GPa, close to that of human bone. However, with increased heat temperature, the yield strength of samples HT950 and HT1000 displayed higher values of 900–1319 MPa, while the hardness increased from 353 ± 10 to 510 ± 25 HV. The elastic strain energy of samples HT950 and HT1000 were also higher in the range of 17.85 and 31.63 MJ/m3. The friction coefficient and 3D morphology were used to characterize the wear properties. Sample HT1000 exhibited the minimum wear depth and COF. However, the Ti–35Nb–7Zr–10Cu alloy exhibited weak antibacterial properties against E. coli because the Cu ion concentrations of the alloy were lower than the minimum inhibitory concentration for E. coli. The precipitation type, morphology and distribution of Cu-bearing precipitation significantly affected the mechanical, wear and antibacterial properties of the Ti–Nb–Zr–Cu alloy.